Acoustic analysis of voice signal: Comparison of four applications software. (February 2018) - Vaz-Freitas, Susana; Pestana, Pedro Melo; Almeida, Vítor; Ferreira, Aníbal
Abstract: Objectives: To describe the results of the acoustic analysis of a database of 90 voice samples with distinct dysphonia levels, using four different – commercial and open source – software programs. Study design: Exploratory, transversal. Methods: The samples were analyzed by four different types of software programs that perform acoustical evaluation – one open source software (Praat) and three commercial ones ( Multi Dimensional Voice Program – MDVP by Kay Elemetrics; VoiceStudio by Seegnal; and Dr. Speech by Tiger Electronics) – for comparison among the most commonly used acoustic measures (frequency, perturbation and noise measures). Results: There is a moderate to strong correlation, positive and statistically significant among the software programs. The mean F0 is not statistically different among the used applications. The other acoustic measures revealed statistically significant differences. Conclusion: Even though it is easier to access software programs and there are numerous proposals for acoustic measures, not all of them are statistically representative nor have numeric semblance among the different applications.